Determinants of paddy farmers' market information-seeking behavior in Soppeng District, Indonesia as implications for adaptive decision making toward sustainable agriculture - MUH. FARREL PRAYOGA ARDIANSYAH; MUSLIM SALAM; MUHAMMAD HATTA JAMIL; RUSLI M. RUKKA; RAHIM DARMA; RIDA AKZAR (Asian Journal of Agriculture, 2026)
Abstract. Ardiansyah MFP, Salam M, Jamil MH, Rukka RM, Darma R, Akzar R. 2026. Determinants of paddy farmers' market information-seeking behavior in Soppeng District, Indonesia as implications for adaptive decision making toward sustainable agriculture. Asian J Agric 10 (1): g100152. https://doi.org/10.13057/asianjagric/g100152. Access to accurate and timely agricultural market information is essential for improving farmers' decision-making, market participation, adoption of sustainable agricultural practices, biodiversity conservation, and their ability to respond to economic and environmental uncertainty, ultimately promoting sustainable agriculture. However, many farmers remain reluctant to seek such information actively. This study aimed to analyze the determinants of paddy farmers' market information-seeking behavior, explicitly distinguishing it from general agricultural information access that dominates existing studies. A cross-sectional survey was conducted with 190 paddy farmers in Soppeng District, South Sulawesi, Indonesia, selected using Cochrans' sampling method. The data were analyzed using descriptive statistics and binary logistic regression. Descriptive results show that farmer groups (30.43%) are the primary source of market information, followed by independent searching (20.11%), extension workers (19.02%), and fellow farmers (18.48%). Logistic regression results indicate that age (β = -0.080; p < 0.05) and farming experience (β = -0.045; p < 0.10) negatively influence information-seeking behavior, while education (β = 0.325; p < 0.01), crop diversification (β = 2.790; p < 0.01), extension contact (β = 0.148; p < 0.10), market distance (β = 0.515; p < 0.10), and credit access (β = 1.273; p < 0.05) have positive effects. The model demonstrates good fit (Hosmer-Lemeshow p = 0.881) and strong explanatory power (Nagelkerke R² = 0.665). These findings suggest that market information seeking is a behavioral response shaped by farmers' capacity, institutional exposure, and incentives to manage price and income uncertainty, rather than by information availability alone, with implications for how farmers adapt their sustainable production, resource use, and marketing strategies under changing economic and environmental conditions for sustainable agriculture goals. This study provides empirical evidence that strengthening behavior-sensitive extension systems, local information intermediaries, and integrated market information services is critical to enhancing farmers' decision-making and supporting sustainable agricultural systems.